Analogous assay between green tea mouthwash, listerine mouthwash and chlorhexidine mouthwash in plaque reduction, on orthodontic patients: a randomized cross-over study - Raju, Ramyathilagam; Divya, Angeline; Rajendran, Ganesh; John, James Rufus (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of the study was to compare the efficiency of green tea mouthwash, Listerine mouthwash and Chlorhexidine mouthwash in plaque reduction among orthodontic patients. Methods: The study employed a double blinded, simple randomized, cross over design with a control group consisting of 30 orthodontic patients undergoing fixed appliance therapy. All the subjects were divided into group 1 (Green tea), group 2 (Listerine) and group 3 (Chlorhexidine) as 10 subjects per group. Gingival status was assessed using Sulcus Bleeding Index and plaque accumulation was assessed using Turesky-Gilmore-Glickman modification of Quigley Hein Index. After a relapse period of 15 days, group 1 and 2 were crossed over, however, group 3 remained the same. Indices were again recorded at baseline and 15th day. Results: The mean gingival and plaque score was reduced in all the three groups. However, green tea mouthwash was estimated to have the highest mean difference from 2.17 ± 0.610 at baseline to 1.48 ± 0.474 on the 15th day. Conclusions: Effective use of mouthwashes as supplements for tooth brushing has proved to be beneficial in oral hygiene and maintenance. The findings of this study provide useful insights on the effectiveness of different compositions of mouthwashes.